Understanding job search intentions: a study on psychological drivers among Malaysian Graduates - Choon, Wei Low; Mah, Pei Yew; Shaari, Nur Fatihah; Shukei, Liew (UiTM Press, 2025)
This study examines the relationship between job search self-efficacy, subjective norms, PBC, attitude, and job search intention among 139 Malaysian undergraduates in the Klang Valley using the Theory of Planned Behaviour (TPB) framework. In recent years, Malaysia has faced increasing challenges of graduate unemployment and skill-related underemployment, raising concerns about students’ readiness to enter the workforce. Understanding the psychological and behavioural factors influencing job search intention is crucial to addressing these issues. The multiple linear regression analysis findings reveal that PBC and attitude significantly and positively influence job search intention. Students with a positive attitude towards job search activities exhibit a higher intention to search, and greater perceived control over the process further strengthens this intention. While subjective norms and job search selfefficacy are positively associated with job search intention, they are not statistically significant predictors. The results highlight the importance of intrinsic factors, such as personal attitudes and control, in shaping job search behaviour. This study recommends that higher education institutions offer targeted career guidance, focusing on resume writing, interview skills, and job market navigation to build students’ confidence. Strengthening engagement in job search activities can improve graduates' employment prospects and contribute to Malaysia’s broader economic development.